2004
DOI: 10.1038/sj.embor.7400243
|View full text |Cite|
|
Sign up to set email alerts
|

The small chemical vacuolin‐1 inhibits Ca2+‐dependent lysosomal exocytosis but not cell resealing

Abstract: Resealing after wounding, the process of repair following plasma membrane damage, requires exocytosis. Vacuolins are molecules that induce rapid formation of large, swollen structures derived from endosomes and lysosomes by homotypic fusion combined with uncontrolled fusion of the inner and limiting membranes of these organelles. Vacuolin-1, the most potent compound, blocks the Ca 2 þ -dependent exocytosis of lysosomes induced by ionomycin or plasma membrane wounding, without affecting the process of resealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 22 publications
10
139
1
1
Order By: Relevance
“…The low micromolar [Ca 2ϩ ] i dependence of their exocytosis expands the range of physiological and pathological processes in which these vesicles could be involved. Some of these processes, cell differentiation and membrane repair, have already been identified (Borgonovo et al, 2002;Cerny et al, 2004). Moreover, the enlargeosome membranes were found to be resistant to nonionic detergents, a property attributed to the existence, in the plane of their membrane, of small microdomains (Ͻ100 nm in diameter), the rafts, rich in cholesterol and sphingolipids (Pralle et al, 2000;Simons and Toomre, 2000;Anderson and Jacobson, 2002;Parton and Hancock, 2004), where specific proteins accumulate in a dynamic equilibrium with the other membrane domains (Kenworthy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low micromolar [Ca 2ϩ ] i dependence of their exocytosis expands the range of physiological and pathological processes in which these vesicles could be involved. Some of these processes, cell differentiation and membrane repair, have already been identified (Borgonovo et al, 2002;Cerny et al, 2004). Moreover, the enlargeosome membranes were found to be resistant to nonionic detergents, a property attributed to the existence, in the plane of their membrane, of small microdomains (Ͻ100 nm in diameter), the rafts, rich in cholesterol and sphingolipids (Pralle et al, 2000;Simons and Toomre, 2000;Anderson and Jacobson, 2002;Parton and Hancock, 2004), where specific proteins accumulate in a dynamic equilibrium with the other membrane domains (Kenworthy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous patchclamp and immunocytochemical studies (Ninomiya et al, 1996;Kasai et al, 1999;Borgonovo et al, 2002;Cerny et al, 2004), the process had not been specifically investigated. Now, we have found that a low-rate endocytosis of d/A-rich patches occurs even in resting cells, presumably as a consequence of spontaneous enlargeosome exocytic events, and that intense endocytosis follows the stimulation-induced exocytic responses.…”
Section: Discussionmentioning
confidence: 99%
“…The method is detailed in Materials and Methods, including lysosomal labeling with FITC-conjugated dextran, intracellular organelle isolation, and flow cytometry analysis. The RT4 Schwann cell line was treated with vacuolin-1 (5 M/L), a reagent known to enlarge lysosomes by an unknown mechanism (Cerny et al, 2004). There was a significant increase of lysosomal sizes in vacuolin-1-treated cells (10.4 Ϯ 1.2 FSC-A values; n ϭ 12 cultures) compared with that in the vehicle-treated cells (5.6 Ϯ 0.6; n ϭ 11; p Ͻ 0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vac1 is a drug described by Cerny et al (Cerny et al, 2004) as a blocker of lysosome-regulated exocytosis (see Huynh and Andrews, 2005). Here, we investigated whether, in the experimental conditions specified by Cerny et al (Cerny et al, 2005), Vac1 does inhibit the IONO-induced discharge of macropinosomes from 10 minute-loaded DCs.…”
Section: Macropinosome Exocytosis Is Inhibited By Vac1mentioning
confidence: 99%